(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2011)
The division of knowledge in universities into the Arts or the Humanities on the one hand and the Sciences on the other, has given rise to the perception that the latter are more important in nation building compared to the former, as seen in the emphasis given by the authorities in the training of expertise, budgeting of research projects and planning of manpower.This paper foregrounds the importance of the Humanities as an academic discipline in a well balanced programme of nation building. This significance lies in the Humanities’ focus on the person as a human being, and arising from that the human civilisation. In order to change the world-view of the authorities the disciplines in the Humanities have to empower themselves through collaboration in their research as there is a great deal of overlapping between them in terms of data and methodology, trends of thought in application of theory, not to mention the basic concepts which flow from one discipline to the other. Collaborating rather than isolating is a powerful method in the generation of new ideas for the development of society. Illustrations are taken from research in linguistics.